2023
DOI: 10.1038/s41467-023-38687-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the Saccharomyces cerevisiae Rpd3L histone deacetylase complex

Avinash B. Patel,
Jinkang Qing,
Kelly H. Tam
et al.

Abstract: The Rpd3L histone deacetylase (HDAC) complex is an ancient 12-subunit complex conserved in a broad range of eukaryotes that performs localized deacetylation at or near sites of recruitment by DNA-bound factors. Here we describe the cryo-EM structure of this prototypical HDAC complex that is characterized by as many as seven subunits performing scaffolding roles for the tight integration of the only catalytic subunit, Rpd3. The principal scaffolding protein, Sin3, along with Rpd3 and the histone chaperone, Ume1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The recent studies on Rpd3S and Rpd3L revealed the complex assemblies and architecture in their apo states. 29 31 Several structural studies have focused on the HDACs’ recognition of nucleosome substrates. 32 , 33 The structure of Sirt6 was believed to be the first HDAC in a complex with an H3 tail substrate in the context of nucleosome.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies on Rpd3S and Rpd3L revealed the complex assemblies and architecture in their apo states. 29 31 Several structural studies have focused on the HDACs’ recognition of nucleosome substrates. 32 , 33 The structure of Sirt6 was believed to be the first HDAC in a complex with an H3 tail substrate in the context of nucleosome.…”
Section: Introductionmentioning
confidence: 99%
“…3b , Supplementary Fig. 5 ), mirroring the interaction seen between Sds3 and the Sin3 HID domain in the Rpd3L complex 18 , 25 . Rco1 A meanders across the surface of Rpd3 via residues 163-190 and complements Rpd3’s β-sheet by contributing an additional β-strand (Rco1 A residues 176-179) (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…3c ). Notably, in the Rpd3L complex, Dep1 engages in similar contacts across the Rpd3 surface but does not augment the Rpd3 β-sheet 18 , 25 (Supplementary Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the structures of these complexes in S. cerevisiae , we also find that the Sin3 Lobe of the Rpd3S is much similar with the ARM2 of the Rpd3L (fig. S13A) ( 15 , 16 ). Furthermore, we try to see whether the nucleosome binding mechanism of Rpd3S could partially extend to the Rpd3L complex.…”
Section: Discussionmentioning
confidence: 99%